Exploring the Adoption of E-Bikes by Different User Groups - Plazier, Paul A.; Weitkamp, Gerd; Berg, Agnes E. Van Den (Frontiers in Built Environment, 2018)
Increased e-bike use can potentially support a shift towards more sustainable and active transport systems. This paper outlines the potential of e-bikes for three user groups that have as yet not fully adopted this mode of transportation: commuters, rural residents and students. For each group, some group-specific advantages and limitations are identified that are likely to shape future e-bike mobility. Then, theoretical and methodological advances in transport geography, mobilities studies and environmental psychology are discussed that may form a backdrop for the empirical study of these groups. Based on this analysis, the use of integrative, mixed-methods research approaches is proposed, which consider potential e-bike mobility as the result of individual decision-making and shaped by social and spatial contexts. This approach may provide a base for the development of effective strategies for promoting the adoption of e-bikes among more diverse user groups.